Perancangan Interior Lobby, Café dan Retail Stadion Futsal di Surabaya - Ryan Honardo Rayawang (Intra, 2017)
Design Interior for Futsal Stadium’s Lobby, Café and Retail in Surabaya is based on the reality of futsal in Indonesia is the most popular sports among the society but only for playing with friends and spend the time during weekend. In fact, futsal is less exposed in terms of professional competitions and achievements of the Indonesian National Team that has a good potential by achieving to the top 10 of Asia region. With these facts, futsal should get more attentions and supports from the society, by build a Futsal Stadium. Furthermore, Futsal Stadium could possibly become city icon and attract the urban society attentions towards futsal. This design aims to support the stadium facilities in order to be able to hold the competition up to the international level and to increase the enthusiasm of the society towards futsal, because with the more support from society, we hope that it might improve the achievement of Indonesian National Team.